Views of Nurse educators on support needs of Recognition of prior learning Nursing students enrolled for Diploma in Nursing at a public Nursing Campus - Moeta, Mabitja (University of Pretoria, 2024)
Dissertation (MSc (Nursing Education))--University of Pretoria, 2023.